Additive manufacturing of nanotube-loaded thermosets via direct ink writing and radio-frequency heating and curing - Sarmah, A.; Desai, S. K.; Crowley, A. G.; Zolton, G. C.; Tezel, G. B.; Harkin, E. M.; Green, M. J.
Direct Ink Writing (DIW)is an extrusion-based additive manufacturing method where the print medium is a liquid-phase 'ink' dispensed out of nozzles and deposited along digitally defined paths. Conventional DIW of thermosetting resins relies on viscosity modifying agents, novel crosslinking chemistries, and/or long curing schedules in an oven. Here we demonstrate the use of a co-planar radio frequency applicator to generate an electric field, which can be used to rapidly heat and cure nano-filled composite resins as they are printed. This method avoids the need for an oven or post-curing step. This process consists of a sequential print-and-cure cycle which allows for printing of high-resolution, multi-layered structures. Every extruded layer is partially cured using RF before depositing the next layer; this allows the printed part to maintain structural integrity. The process enables both increased throughput and decreased touch time relative to traditional manufacturing. Commercial epoxy resin with varied nano-filler loadings were examined as DIW candidates. After printing, the thermo-mechanical properties, surface finish, and shape retention of RF-cured samples were comparable to conventionally cured samples. This method of manufacturing establishes RF heating as a suitable alternative to conventional methods, facilitating rapid, free-form processing of thermosetting resins without a mold.
Keywords: DIRECT INK WRITING; RADIO FREQUENCY HEATING; THERMOSETTING RESIN; FREE-FORM PROCESSING